"Who shall be lord of the earth?" Nietzsche, Schmitt, and thinking "beyond the line". (October 2021) - Shapiro, Gary
Carl Schmitt privately acknowledged that his late theory of Erd-Herrschaft (hegemony of the Earth) converged with some of Nietzsche's thought, yet remained silent on this in his book The Nomos of the Earth . This essay reconstructs an implicit Nietzsche–Schmitt dialog, focusing on their related but distinct geopolitical and phenomenological concepts of Earth, the role of binary divisions in ethics and politics, and the nature of hegemony. Nietzsche and Schmitt both derive from a tradition of political theology that relies on the antitheses of state sovereignty and the Antichrist, but they draw opposed conclusions from this duality.